2004
DOI: 10.1093/pasj/56.6.1041
|View full text |Cite
|
Sign up to set email alerts
|

Subaru/HDS Abundances in Three Giant Stars in the Ursa Minor Dwarf Spheroidal Galaxy

Abstract: With the HDS (High Dispersion Spectrograph) on the Subaru telescope, we obtained high resolution optical region spectra of three red giant stars (cos 4, cos 82, and cos 347) in the Ursa Minor dwarf spheriodal galaxy. Chemical abundances in these stars have been analysed for 26 elements including α-, iron-peak, and neutron capture elements. All three stars show low abundances of α-elements (Mg, Si, and Ca) and two stars (cos 82 and cos 347) show high abundance of Mn compared to Galactic halo stars of similar me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
126
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(141 citation statements)
references
References 36 publications
13
126
0
2
Order By: Relevance
“…These measurements show a general trend of lower [α/Fe] ratios at a given [Fe/H] than what is found in Galactic halo stars of comparable metallicity (e.g., Shetrone et al 2001;Fulbright 2002;Tolstoy et al 2003;Sadakane et al 2004;Geisler et al 2005;Monaco et al 2005;Sbordone et al 2007, Koch et al 2007d. Moreover, there is a lack of extremely metal-poor stars in all dSphs studied in detail so far, i.e., very few stars more metal-poor than [Fe/H] = −2.5 dex have been found (Helmi et al 2006;Koch et al 2007a).…”
Section: Detailed Chemical Abundancessupporting
confidence: 53%
“…These measurements show a general trend of lower [α/Fe] ratios at a given [Fe/H] than what is found in Galactic halo stars of comparable metallicity (e.g., Shetrone et al 2001;Fulbright 2002;Tolstoy et al 2003;Sadakane et al 2004;Geisler et al 2005;Monaco et al 2005;Sbordone et al 2007, Koch et al 2007d. Moreover, there is a lack of extremely metal-poor stars in all dSphs studied in detail so far, i.e., very few stars more metal-poor than [Fe/H] = −2.5 dex have been found (Helmi et al 2006;Koch et al 2007a).…”
Section: Detailed Chemical Abundancessupporting
confidence: 53%
“…Studies of abundances in individual stars in dwarf galaxies do not often report stars with light-element abundances similar to secondgeneration globular cluster stars. In Shetrone et al (2003) there is only one star out of the 15 surveyed (Fornax 21) with even mildly elevated [Na/Fe], Sadakane et al (2004) found fairly low [Na/Fe] abundances in the three stars they observed in Ursa Minor, and Geisler et al (2005) find the same result for nine RGB stars in Sculptor. Koch et al (2008) also report one star in Carina (of eight with measured sodium abundance) with moderate [Na/Fe], and Letarte et al (2010) report one star in Fornax (of 70 with measured sodium abundances) with moderate [Na/Fe], but neither study finds any stars with the level of sodium abundance enhancement typically found in second-generation globular cluster stars (e.g., Carretta et al 2009).…”
Section: Stellar Distancesmentioning
confidence: 68%
“…also include, for comparison, Galactic stars from the compilation of Venn et al (2004;and references therein) and Milky Way dSph satellites including the more luminous dSphs (Shetrone et al 2001(Shetrone et al , 2003(Shetrone et al , 2009Fulbright et al 2004;Sadakane et al 2004;Geisler et al 2005;Aoki et al 2009;Cohen & Huang 2009;Frebel et al 2010a;Letarte et al 2010;Tafelmeyer et al 2010;Lemasle et al 2012;Venn et al 2012;and Starkenburg et al 2012) and the most recent measurements in a few ultrafaint dSphs (K08; Feltzing et al 2009;Frebel et al 2010b;Norris et al 2010b;Simon et al 2010;and Gilmore et al 2013). The Ba abundances and limits are very low, at a mean [Ba/H] of −3.97 from the three EW measurements, and [Ba/H] < −3.84 (2σ), <−3.55 (3σ), respectively.…”
Section: Resultsmentioning
confidence: 99%